2021
DOI: 10.1021/acs.jpca.1c00068
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonic Coupling Revealed by the Vibrational Spectra of Solvated Protonated Methanol: Fermi Resonance, Combination Bands, and Isotope Effect

Abstract: Intriguing vibrational features of solvated protonated methanol between 2400−3800 cm −1 are recorded by infrared predissociation spectroscopy. Positions of absorption bands corresponding to OH stretching modes are sensitive to changes in solvation environments, thus leading to changes in these vibrational features. Two anharmonic coupling mechanisms, Fermi resonance (FR) contributed by bending overtones and combination band (CB) associated with intermolecular stretching modes, are known to lead to band splitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…However, owing to the non-negligible magnitude of coupling constants, these overtone and combination tone states become visible in the spectra through effective intensity borrowing from the stretching fundamental states which carry the major oscillator strength. 38,40,48…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, owing to the non-negligible magnitude of coupling constants, these overtone and combination tone states become visible in the spectra through effective intensity borrowing from the stretching fundamental states which carry the major oscillator strength. 38,40,48…”
Section: Resultsmentioning
confidence: 99%
“…However, owing to the non-negligible magnitude of coupling constants, these overtone and combination tone states become visible in the spectra through effective intensity borrowing from the stretching fundamental states which carry the major oscillator strength. 38,40,48 We have found that the anharmonic couplings are intrinsic properties of these cations. The solvation environments would alter the magnitudes of these FR couplings but to a limited extent.…”
Section: B Resemblance In Spectra Of Two-water-solvated and Twobisulf...mentioning
confidence: 95%
See 3 more Smart Citations